From a quantum mechanical description of the assembly processes in microtubules to their semiclassical nonlinear dynamics - Rezania, Vahid; Tuszynski, Jack A. (My University, 2007)
In this paper a quantum mechanical description of the assembly/disassembly process for microtubules is proposed. We introduce creation and annihilation operators that raise or lower the microtubule length by a tubulin layer. Following that, the Hamiltonian and corresponding equations of motion are derived that describe the dynamics of microtubules. These Heisenberg-type equations are then transformed to semi-classical equations using the method of coherent structures. The latter equations are very similar to the phenomenological equations that describe dynamic instability of microtubules in a tubulin solution.
Keywords: microtubules